Development of mapping populations for genetic analysis in yams (Dioscorea rotundata and D. alata) - Sartie, A.M.; Asiedu, Robert (2011)
Progress is being made at the International Institute for Tropical Agriculture to develop molecular tools for marker-assisted selection that would complement and expedite conventional breeding approaches for genetic improvement of yams (Dioscorea spp.). F1 mapping populations were developed from crossing male and female parents of D. rotundata Poir. and D. alata Lam. that differ in specific traits of interest towards identification of molecular markers linked to those traits. Success in hybridization was validated based on DNA analysis with SSR markers on agarose gel. Traits for which the populations were developed included multiple tuber production and cooking quality in D. rotundata, and anthracnose disease, cooking quality and tuber oxidation in D. alata. Death of plants in the field and rotting of tubers in storage, possibly due to pests, diseases and other environmental factors were encountered that led to the reduction in size of the populations. Low seed multiplication ratio necessitates two to three cycles of tuber multiplication of mapping population genotypes to achieve adequate numbers of seed tubers for field experimentation. These mapping populations are valuable tools for genetic analysis and molecular marker development in yam improvement programmes.